Preventing Recurrence in Clean and Contaminated Hernias Using Biologic Versus Synthetic Mesh in Ventral Hernia Repair: The PRICE Randomized Clinical Trial. Issue 4 (April 2021) - Harris, Hobart W.; Primus, Frank; Young, Charlotte; Carter, Jonathan T.; Lin, Matthew; Mukhtar, Rita A.; Yeh, Benjamin; Allen, Isabel E.; Freise, Chris; Kim, Esther; Sbitany, Hani; Young, David M.; et al.
Abstract : Objective: The aim of this study was to evaluate which mesh type yields lower recurrence and complication rates after ventral hernia repair. Summary Background Data: More than 400, 000 ventral hernia repairs are performed annually in the United States. Although the most effective method for repairing ventral hernias involves using mesh, whether to use biologic mesh versus synthetic mesh is controversial. Methods: Single-blind, randomized, controlled, pragmatic clinical trial conducted from March 2014 through October 2018; 165 patients enrolled with an average follow up of 26 months. Patients were randomized 1:1 to have their ventral hernias repaired using either a biologic (porcine) or synthetic (polypropylene) mesh. The primary study outcome measure was hernia recurrence at 2 years. Results: A total of 165 patients (68 men), mean age 55 years, were included in the study with a mean follow-up of 26 months. An intention-to-treat analysis noted that hernias recurred in 25 patients (39.7%) assigned to biologic mesh and in 14 patients (21.9%) assigned to synthetic mesh ( P = 0.035) at 2 years. Subgroup analysis identified an increased rate of hernia recurrence in the biologic versus the synthetic mesh group under contaminated wound conditions (50.0% vs 5.9%; P for interaction = 0.041). Postoperative complication rates were similar for the 2 mesh types. Conclusions: The risk of hernia recurrence was significantly higher for patients undergoing ventral hernia repair with biologic mesh compared to synthetic mesh, with similar rates of postoperative complications. These data indicate that the use of synthetic mesh over biologic mesh to repair ventral hernias is effective and can be endorsed, including under contaminated wound conditions. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT02041494.